Beyond Higher Education: University Establishments and Childhood Maltreatment - Yanjun Li; Xinyan Liu; Ryuichi Tanaka (Global Labor Organization (GLO), 2025)
Violence against children, especially trafficking, is a global concern. This paper proposes that nearby educational institutions can help reduce such violence. Using a quasi-experiment in China from 1999, where university campuses were exogenously established, the study shows that these institutions led to fewer trafficked children. The mechanism involves economic development, improved public safety, and changes in family behavior, ultimately reducing child trafficking. The findings highlight that the establishment of social facilities, such as universities, can unintentionally enhance children's safety and well-being by improving the surrounding community's economic and social conditions.
Keywords: H54; K42; O15; O18; R23; J13; 330; Childhood Maltreatment; Child trafficking; Illegal behaviors; University expansion policy